International standards for monoclonal antibodies for assessing the biological activity of medicines: A status update - L. A. Gayderova; N. A. Alpatova; S. L. Lysikova; M. L. Baykova; A. M. Guskov; D. A. Zubkov (Биопрепараты: Профилактика, диагностика, лечение)
Scientific relevance. The clinical effects and the expiration of patents for original (reference) biotechnological medicines based on monoclonal antibodies (mAbs) stimulated the development of biosimilar mAbs. The quality profile of a biosimilar mAb should correspond to the quality of the reference medicinal product. When demonstrating biosimilarity and determining the activity of medicines as part of batch quality control, analysts should study the biological properties of mAbs using suitable reference standards. The lack of international standards (ISs) makes mAb manufacturers use in-house reference standards. There is a risk of obtaining non-uniform quality and efficacy data because of the use of in-house reference standards, the heterogeneity and structural complexity of mAbs, and the relationship between the biological activity and efficacy of mAbs.Aim. This study aimed to analyse the relevance of and need for ISs for the biological activity of biotherapeutic mAbs and to define the role of reference medicinal products and ISs in assessing biosimilarity and testing medicines throughout their lifecycle.Discussion. This review covers the issues arising from the lack of ISs for assessing the biological activity of mAbs and the role and significance of reference products and ISs for biosimilars. The authors describe the specifics of studying the biological properties of mAbs and summarise the data on the need to develop and use ISs for the standardisation of biological tests. This review presents the results of studies on the first ISs established by the World Health Organisation to assess the biological activity of mAbs; these results suggest the need to standardise mAbs using ISs to ensure the quality, safety, and efficacy of mAb therapy.Conclusions. The use of ISs for mAbs plays a key role in harmonising biological activity assessments. Publicly available ISs serve as primary standards for the calibration of secondary reference materials. Moreover, ISs are required for the harmonisation of activity evaluation (in IU) between laboratories and for the consistency of the activity of various medicinal products from different manufacturers that share the same INN. The use of ISs by mAb manufacturers will contribute to ensuring the quality of mAbs and clinical monitoring of the effectiveness of their use.